Transfiguracja symboli archetypowych w utworach Marty Tomaszewskiej - Miernik, Agnieszka (Studia Europaea Gnesnensia, 2016)
An analysis of the process concerning transfer of archetypal symbols in fairy-tale plots, conducted firom the perspective of depth psychology (C.G. Jung), reveals the human being to be a culture creator (homo culturalis), who uses vivid language and aims at abstracting a multidimensional sense of existence. The paradigm of archetypal literary criticism (N. Frye) offers multidimensional insights into a work of literature and demonstrates the shifts of the arche, a constant adjustment of archetypes to the demands of the present. When attempting to determine the archetypal order in the works of Marta Tomaszewska, one should be aware of the fact that it is one of many possible efforts to read multi-perspective symbolic contents and it validates the thesis presuming an endless source of the collective unconscious.